Differences in intervention for patients with acute stroke according to the manpower of neurosurgeons - Hyeong Sook Kim; Yun Seo Jang; Suk-Yong Jang; Chung Mo Nam; Eun-Cheol Park (PLoS ONE, 2025)
Background and objectives Stroke, a leading global cause of death, poses a substantial health burden. The incidence of stroke is high in an aging society. Appropriate healthcare resources are crucial for providing prompt interventions to patients with stroke. We investigated the factors associated with the choice between conservative and interventional treatments, including an analysis of the number of neurosurgeons required for interventional care, for patients with acute stroke. Methods We utilized health insurance claims data from hospitals submitted to the Health Insurance Review and Assessment Service in 2018 and 2021. The data covered 60,661 patients with acute stroke admitted to the emergency room in tertiary or general hospitals. The number of hospital neurosurgeons was the key variable of interest; conservative and interventional treatments were the independent variables. Using a multi-level analysis, we identified the individual- and hospital-level factors associated with interventional treatment by constructing four models. Results The odds of patients with hemorrhage and ischemic stroke receiving intervention were 0.60 [95% confidence interval (CI), 0.31–0.52] and 0.51 [95% CI, 0.39–0.65] times lower, respectively, in the group with fewer neurosurgeons. We categorized the number of neurosurgeons and indicated an association between a minimum of three neurosurgeons and stroke treatment. Conclusion We demonstrated an association between individual- and hospital-level factors and the intervention for patients with different types of stroke. We predicted the number of neurosurgeons needed for intervention. These findings can be used for the efficient distribution and utilization of healthcare resources to improve public health.